ASSURANCE, EMPHATY, TANGIBLES) TERHADAP KEPUASAN PELANGGAN PADA PT AETRA DI JAKARTA. - Yolanda dan Novhani Tamara (Jurnal Manajemen FE-UB, 2015)
This research entitled "The Effect of Quality service Reliability, Resvonsivenes, Assurance, Emphaty, Tangibles to Customer Satisfaction PT. Aetra in Jakarta ". The purpose of this study is to analyze the influence of simultaneous and partial Reliability, Resvonsiveness, Assurance, Emphaty, Tangibles to Customer Satisfaction PT. Aetra in Jakarta.The variables that theoretically influence the relationship between the independent variable to the Dependent variable is the interverning variable which in this case, is as observed variable and able to directly correlate between the Independent variables (Reliability, Resvonsiveness, Assurance, Emphaty, Tangibles) to Dependent variable (Customer Satisfaction) . By taking samples of 80 Customers PT. Aetra in Jakarta.To solve the problem by analyzing and testing the relationship and influence between independent variable to dependent variable used causal model through path analysis (Path Analisys) with the help of SPSS 22.0. Keywords: Reliability, Resvonsivenes, Assurance, Emphaty, Tangibles to Customer Satisfaction